HIV infection among heterosexual travellers attending the Hospital for Tropical Diseases, London. Issue 5 (October 1992) - Hawkes, S; Malin, A; Araru, T; Mabey, D
Abstract : OBJECTIVE--To determine the prevalence of HIV infection in travellers attending the Hospital for Tropical Diseases, London, and to assess correlates and behavioural risk factors for infection. DESIGN--All patients tested for HIV infection during a 28-month period were included. Information was obtained from clinical records and standardised serological request forms. SETTING--Hospital for Tropical Diseases, London, UK. SUBJECTS--298 patients (in-patient and out-patient) were tested. RESULTS--258 of those tested were exclusively heterosexual and not injecting drug users. 5.4% of these were HIV-1 antibody positive. Rates in those originating from the UK and those from outside the UK were 1.8% and 33.2% respectively. Most non-UK citizens were symptomatic when tested; UK citizens were generally tested as part of a routine screening, therefore the two groups are not comparable. Rates of risk behaviour were high in both groups. CONCLUSION--The rate of HIV infection in heterosexual travellers was 5.4%. Amongst UK citizens the rate was 1.8%. All travellers should be made aware of the potential risk of acquiring HIV infection through sexual contact.